Dietary fructose in relation to blood pressure and serum uric acid in adolescent boys and girls - Bobridge, K.; Haines, G.; Mori, T.; Beilin, L.; Oddy, W.; Sherriff, Jillian; O'Sullivan, T. (Nature Publishing Group, 2013)
Evidence that fructose intake may modify blood pressure is generally limited to adult populations. This study examined cross-sectional associations between dietary intake of fructose, serum uric acid and blood pressure in 814 adolescents aged 13–15 years participating in the Western Australian Pregnancy Cohort (Raine) Study. Energy-adjusted fructose intake was derived from 3-day food records, serum uric acid concentration was assessed using fasting blood and resting blood pressure was determined using repeated oscillometric readings. In multivariate linear regression models, we did not see a significant association between fructose and blood pressure in boys or girls. In boys, fructose intake was independently associated with serum uric acid (P<0.01), and serum uric acid was independently associated with systolic blood pressure (P<0.01) and mean arterial pressure (P<0.001). Although there are independent associations, there is no direct relationship between fructose intake and blood pressure. Our data suggest that gender may influence these relationships in adolescence, with significant associations observed more frequently in boys than girls.